2019
DOI: 10.1016/j.cub.2019.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Costs of Meiotic Drivers

Abstract: In sexual reproduction, opportunities are limited and the stakes are high. This inevitably leads to conflict. One pervasive conflict occurs within genomes between alternative alleles at heterozygous loci. Each gamete and thus each offspring will inherit only one of the two alleles from a heterozygous parent. Most alleles 'play fair' and have a 50% chance of being included in any given gamete. However, alleles can gain an enormous advantage if they act selfishly to force their own transmission into more than ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 125 publications
4
58
0
Order By: Relevance
“…Further, SPG6 includes type spermatogonial cells transitioning to preleptotene spermatocytes based on the expression of conserved meiotic genes, such as PRDM9, ZCWPW1, and REC8. In addition to the known, classic meiotic genes, our dataset uncovers many primate-specific genes (i.e., lacking mouse orthologs) that are active in human and macaque SPG6, including the simianspecific Variably Charged (VC) gene family (VCX, VCX2, VCX3A, VCX3B) 94 , which is an X chromosome multi-copy gene family theorized to play a role in meiotic drive 94,95 . Recent studies have shown that VCX may be regulated by PRDM9 96 , further underscoring its potential role in meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SPG6 includes type spermatogonial cells transitioning to preleptotene spermatocytes based on the expression of conserved meiotic genes, such as PRDM9, ZCWPW1, and REC8. In addition to the known, classic meiotic genes, our dataset uncovers many primate-specific genes (i.e., lacking mouse orthologs) that are active in human and macaque SPG6, including the simianspecific Variably Charged (VC) gene family (VCX, VCX2, VCX3A, VCX3B) 94 , which is an X chromosome multi-copy gene family theorized to play a role in meiotic drive 94,95 . Recent studies have shown that VCX may be regulated by PRDM9 96 , further underscoring its potential role in meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, many eukaryotic genomes contain 'selfish' elements that bias their own transmission such that they are overrepresented in the viable gametes [2][3][4]. These loci are known as meiotic drivers and they can both directly and indirectly reduce fitness through a number of mechanisms (reviewed in [5,6]).…”
Section: Introductionmentioning
confidence: 99%
“…However, many eukaryotic genomes contain ‘selfish’ elements that bias their own transmission into the viable gametes generated by a heterozygote (2–4). These loci are known as meiotic drivers and they can directly and indirectly reduce fitness through a number of mechanisms (reviewed in (5, 6)).…”
Section: Introductionmentioning
confidence: 99%